Development of authentic assessment of 21st-century skills in Kurikulum Merdeka - Neneng Widya Sopa Marwa; Pajar Reza Pitria; Faisal Madani (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Kurikulum Merdeka has impacted educational progress in Indonesia, and authentic assessments are needed to ensure holistic and relevant evaluation of student learning progress. This research aims to analyze the importance of developing authentic assessments of 21st-century skills in implementing Kurikulum Merdeka in elementary schools. This research method uses the Systematic Literature Review (SLR) research method; the SLR stages consist of planning, implementation, and reporting. After searching on Google Chrome and the Google Scholar site, 24 articles were obtained relating to the discussion of authentic assessment of 21st-century skills in Kurikulum Merdeka in elementary schools. The 24 articles were then analyzed based on the criteria for determining the quality of the study material so that ten articles were obtained. Based on the results of the criteria analysis. The analysis involved identifying 21st-century skills essential to developing and understanding the benefits and challenges of implementing authentic assessment in learning. The results of this research show that the development of authentic assessment has an essential role in learning in elementary schools. Authentic assessment allows assessments that involve the application of students' knowledge and skills in real-life situations, creating a close connection between school learning and everyday life. AbstrakKurikulum Merdeka telah memberikan dampak terhadap kemajuan pendidikan di Indonesia, pengembangan asesmen otentik diperlukan untuk memastikan evaluasi yang holistik dan relevan terhadap kemajuan belajar siswa. Penelitian ini bertujuan untuk melakukan analisis mengenai pentingnya mengembangkan asesmen autentik keterampilan abad 21 dalam konteks implementasi Kurikulum Merdeka di sekolah dasar. Metode penelitian ini menggunakan metode penelitian Systematic Literature Review (SLR), tahapan SLR tersendiri terdiri dari perencanaan, pelaksanaan dan pelaporan. Setelah melakukan pencarian pada google chrome dan situs google scholar, diperoleh 24 artikel yang berkaitan dengan bahasan asesmen autentik keterampilan abad 21 pada Kurikulum Merdeka di sekolah dasar. 24 artikel tersebut kemudian dianalisis berdasarkan kriteria penentuan kualitas bahan kajian sehingga diperoleh 10 artikel. berdasarkan hasil analisis kriteria. Analisis tersebut melibatkan identifikasi keterampilan abad 21 yang penting untuk dikembangkan, serta pemahaman tentang manfaat dan tantangan asesmen autentik dalam pembelajaran. Hasil dari penelitian tersebut menunjukan pengembangan asesmen autentik memiliki peranan penting dalam pembelajaran di sekolah dasar. Asesmen autentik memungkinkan penilaian yang melibatkan aplikasi pengetahuan dan keterampilan siswa dalam situasi kehidupan nyata, menciptakan hubungan yang erat antara pembelajaran di sekolah dengan kehidupan sehari-hari.Kata Kunci: Asesmen autentik; pendidikan abad 21; kurikulum merdeka